2021
DOI: 10.5935/1518-0557.20210028
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural analysis of Lyophilized Human Spermatozoa

Abstract: These results were presented at the 35 th annual meeting of the European Society of Human Reproduction and Embryology ABSTRACT Objective: Lyophilization is potentially more practical and cost-effective alternative for sperm preservation. However, there are no studies that evaluate the ultrastructure of human spermatozoa after lyophilization. Therefore, the aim of our study was to evaluate the ultrasctructure of lyophilized spermatozoa using Transmission Electron Microscopy.Methods: From a total of 21 donated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 48 publications
0
5
0
3
Order By: Relevance
“…Overall damage of plasma membrane in lyophilized sheep lymphocytes (analyzed by transmission electron microscopy) or spin-dried human hepatoma cells (HepG2; analyzed by using Syto-13 and ethidium bromide viability dyes) had already been reported (Iuso et al, 2013;. Ruptures of the plasma membrane in dehydrated sperm from species as diverse as men (Bossi et al, 2021;Gianaroli et al, 2012), llamas (Carretero et al, 2020), or cattle (Sitaula et al, 2009) also have been observed. It is also interesting to note that lyophilization of horse sperm appears to induce less membrane damage (a higher percentage of cells with nonperoxidized lipid and nonpermeable membrane) than cryopreservation (Restrepo et al, 2019).…”
Section: Impact On the Cytoplasmic Membranes Organelles And Gamete Fu...mentioning
confidence: 99%
See 2 more Smart Citations
“…Overall damage of plasma membrane in lyophilized sheep lymphocytes (analyzed by transmission electron microscopy) or spin-dried human hepatoma cells (HepG2; analyzed by using Syto-13 and ethidium bromide viability dyes) had already been reported (Iuso et al, 2013;. Ruptures of the plasma membrane in dehydrated sperm from species as diverse as men (Bossi et al, 2021;Gianaroli et al, 2012), llamas (Carretero et al, 2020), or cattle (Sitaula et al, 2009) also have been observed. It is also interesting to note that lyophilization of horse sperm appears to induce less membrane damage (a higher percentage of cells with nonperoxidized lipid and nonpermeable membrane) than cryopreservation (Restrepo et al, 2019).…”
Section: Impact On the Cytoplasmic Membranes Organelles And Gamete Fu...mentioning
confidence: 99%
“…However, this observation was not confirmed in microwave‐dried cat sperm that kept normal centrosomal functions (Patrick et al, 2017). A recent study comparing cryopreservation versus lyophilization in human sperm demonstrated that freezing induces more lesions to the mid‐piece with some mitochondria degeneration and rupture of the plasma membrane (Bossi et al, 2021). However, analysis by transmission electron microscopy showed that lyophilized sperm heads have ruptured plasma membranes, absence of acrosomes, and nuclei with heterogeneous and decondensed chromatin.…”
Section: Damages and Stresses On Biological Structures And Functions ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility that vitrified sperm preserve their function at temperature of −80°C could simplify storage, optimizing the space and time as well as the operator's safety [3]. Lyophilization of spermatozoa is another method that requires additional investigation and validation [20]. Since the lyophilized spermatozoa are immobile, they can only be used in intracytoplasmic sperm injection (ICSI).…”
Section: Storage Of the Vitrified Sperm Samplesmentioning
confidence: 99%
“… 69 Several reports on freeze-drying of animal spermatozoa have been published; however, because of ethical limitations or other unpublished reasons, ICSI has not been performed using freeze-dried human spermatozoa. 70 71 Studies on the dry preservation of human spermatozoa showed that the survival and maneuverability membrane of sperm were completely impaired after being freeze-dried; 72 however, the chromatin structure of spermatozoa and the protoplast structure in the sperm head were retained. 71 …”
Section: Preservation Of Spermatozoa In the Experimental Stagementioning
confidence: 99%